Beyond Attention Effects: Modeling the Persuasive and Emotional Effects of Advertising Creativity - Yang, Xiaojing; Smith, Robert E. (Marketing Science, 2009)
While creativity in advertising is a growing area of marketing research, relatively little is known about how the effects of creativity are produced. Accordingly, this research explores the basic persuasive (i.e., desire to postpone closure) and emotional (i.e., positive affect) mechanisms through which creative ads exert their influence on consumer viewing and purchase intentions. In addition, the model hypothesizes that the level of involvement with the ad moderates the desire to postpone closure effects but not the emotional impact. An overall model of the impact of ad creativity is developed and tested using structural equations analysis. Results from three experiments show the model receives good support.